Effects of Phytoestrogens on the Developing Brain, Gut Microbiota, and Risk for Neurobehavioral Disorders - Rosenfeld, Cheryl S. (Frontiers in Nutrition, 2019)
Many pregnant and lactating women consume high amounts of soy and other plant products that contain phytoestrogens, such as genistein and daidzein. Infants may also be provided soy-based formulas. With their ability to bind and activate estrogen receptors (ESR) in the brain, such compounds can disrupt normal brain programming and lead to later neurobehavioral disruptions. However, other studies suggest that maternal consumption of soy and soy-based formulas containing such chemicals might lead to beneficial behavioral effects. Select gut microbes might also convert daidzein and to a lesser extent genistein to even more potent forms, e.g., equol derivatives. Thus, infant exposure to phytoestrogens might lead to contrasting effects dependent upon the gut flora. It is also becoming apparent that consumption or exposure to these xenoestrogens may lead to gut dysbiosis. Phytoestrogen-induced changes in gut bacteria might in turn affect the brain through various mechanisms. This review will consider the evidence to date in rodent and other animal models and human epidemiological data as to whether developmental exposure to phytoestrogens, in particular genistein and daidzein, adversely or beneficially impact offspring neurobehavioral programming. Consideration will be given to potential mechanisms by which such compounds might affect neurobehavioral responses. A better understanding of the effects perinatal exposure to phytoestrogen may have on brain programming will permit pregnant women and those seeking to become pregnant to make better educated choices. If gut dysbiosis is responsible for some of such changes, it may also pave the way to potential remediation strategies, namely pre-, pro-, or post-biotics.